Variation in runoff with age of Chinese fir plantations in Central South China - Tian, Dalun; Yan, Wende; Chen, Xiaoyong; Deng, Xiangwen; Peng, Yuanying; Kang, Wenxing; Peng, Changhui (Hydrological Processes, 2008)
Abstract To determine the influence of forest structures on runoff characteristics, the hydrological effects of Chinese fir plantations were studied by analysing runoff patterns at different growth and development stages (stand age classes I to V) from 1984 to 2004 at the Huitong Ecosystem Research Station, Central South University of Forestry and Technology, Hunan Province, Central South China. Results for two small experimental Chinese fir watersheds showed different peak values for surface runoff amount and coefficients at different ages, with lowest values in age classes I and V and highest values in age classes II and III. However, both underground and total runoff coefficients decreased with increasing age class. Total runoff coefficient was about twice as high in age class I (30·8%) as that in age class V (15·8%). Higher underground and total runoff coefficients were found in young forests. This was mainly attributed to soil disturbance due to human management practices such as site ploughing. Results indicate that Chinese fir plantations play a significant role in regulating water distribution in the watershed. Useful information is provided on the effects of forest management practices on hydrological processes in forest plantations. Copyright © 2008 John Wiley & Sons, Ltd.

Chapter Eighteen Uncertainty and Sensitivity Issues in Process-based Models of Carbon and Nitrogen Cycles in Terrestrial Ecosystems - Larocque, G.R.; Bhatti, J.S.; Gordon, A.M.; Luckai, N.; Wattenbach, M.; Liu, J.; Peng, C.; Arp, P.A.; Liu, S.; Zhang, C.-F.; Komarov, A.; Grabarnik, P.; et al. (Developments in Integrated Environmental Assessment, 2008)

Micrometeorological measurements of nitrous oxide exchange above a cropland - Li, Jun; Tong, Xiaojuan; Yu, Qiang; Dong, Yunshe; Peng, Changhui (Atmospheric Environment, 2008)

Sectoral approaches to improve regional carbon budgets - Smith, Pete; Nabuurs, Gert-Jan; Janssens, Ivan A.; Reis, Stefan; Marland, Gregg; Soussana, Jean-François; Christensen, Torben R.; Heath, Linda; Apps, Mike; Alexeyev, Vlady; Fang, Jingyun; Gattuso, Jean-Pierre; et al. (Climatic Change, 2008)

Leaf δ13 C reflects ecosystem patterns and responses of alpine plants to the environments on the Tibetan Plateau - Song, Minghua; Duan, Deyu; Chen, Hui; Hu, Qiwu; Zhang, Feng; Xu, Xingliang; Tian, Yuqiang; Ouyang, Hua; Peng, Changhui (Ecography, 2008)
Leaf δ 13 C is an indicator of water‐use efficiency and provides useful information on the carbon and water balance of plants over longer periods. Variation in leaf δ 13 C between or within species is determined by plant physiological characteristics and environmental factors. We hypothesized that variation in leaf δ 13 C values among dominant species reflected ecosystem patterns controlled by large‐scale environmental gradients, and that within‐species variation indicates plant adaptability to environmental conditions. To test these hypotheses, we collected leaves of dominant species from six ecosystems across a horizontal vegetation transect on the Tibetan Plateau, as well as leaves of Kobresia pygmaea (herbaceous) throughout its distribution and leaves of two coniferous tree species ( Picea crassifolia, Abies fabri ) along an elevation gradient throughout their distribution in the Qilian Mountains and Gongga Mountains, respectively. Leaf δ 13 C of dominant species in the six ecosystems differed significantly, with values for evergreen coniferous<evergreen broadleaved tree<alpine shrub<sedges∼graminoid<xeromorphs. Leaf δ 13 C values of the dominant species and of K. pygmaea were negatively correlated with annual precipitation along a water gradient, but leaf δ 13 C of A. fabri was not significantly correlated with precipitation in habitats without water‐stress. This confirms that variation of δ 13 C between or within species reflects plant responses to environmental conditions. Leaf δ 13 C of the dominant species also reflected water patterns on the Tibetan Plateau, providing evidence that precipitation plays a primary role in controlling ecosystem changes from southeast to northwest on the Tibetan Plateau.

Simulating carbon exchange of Canadian boreal forests - Sun, Jianfeng; Peng, Changhui; McCaughey, Harry; Zhou, Xiaolu; Thomas, Valerie; Berninger, Frank; St-Onge, Benoît.; Hua, Dong (Ecological Modelling, 2008)

Ecosystem service value assessment for constructed wetlands: A case study in Hangzhou, China - Yang, Wu; Chang, Jie; Xu, Bin; Peng, Changhui; Ge, Ying (Ecological Economics, 2008)

TRIPLEX model testing and application for predicting forest growth and biomass production in the subtropical forest zone of China's Zhejiang Province - Zhang, Jun; Chu, Ziyan; Ge, Ying; Zhou, Xiaolu; Jiang, Hong; Chang, Jie; Peng, Changhui; Zheng, Jiawen; Jiang, Bo; Zhu, Jinru; Yu, Shuquan (Ecological Modelling, 2008)

Simulating carbon exchange in Canadian Boreal forests - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai; Sun, Jianfeng; Wu, Haibin; Hua, Dong (Ecological Modelling, 2008)